Transcript-activated collagen matrix for enhanced bone marrow stem cell differentiation and osteochondral repair - Gang Zhong; Yixuan Luo; Meng Wang; Zhengran Yu; Xuenong Zou; Gang Wang; Fei Chen; Yin Yu (Engineered Regeneration)
The regeneration of critical-sized osteochondral defects remains a significant challenge due to the limited self-healing capacity of cartilage. Traditional approaches, such as autologous chondrocyte implantation (ACI) and matrix-induced autologous chondrocyte implantation (MACI), have shown promise but are limited by issues like insufficient cell availability, dedifferentiation of chondrocytes during expansion, and the formation of fibrocartilage rather than functional hyaline cartilage. This study presents a promising approach utilizing transcript-activated matrices (TAMs) with mRNA to enhance the therapeutic potential of bone marrow mesenchymal stem cells (BMSCs) in situ. Chemically modified mRNA (cmRNA) encoding transforming growth factor β3 (TGF-β3) was encapsulated in a collagen hydrogel to provide localized, sustained delivery of chondrogenic signals. In a rat model of critical-sized osteochondral defects, this strategy significantly promoted cartilage regeneration, achieving structural and molecular restoration within six weeks. Histological and biochemical analyses revealed robust chondrogenesis, enhanced extracellular matrix deposition, and superior mechanical properties. Moreover, TAM therapy maintained subchondral bone integrity This work highlights the transformative potential of mRNA-activated matrices as a platform technology that not only addresses key limitations of existing cartilage repair strategies but also provides a biomimetic microenvironment that guides stem cell differentiation and tissue regeneration.